Stranded steel wire ropes Part 6. Specification for ropes for mine hoisting - British Standards Institution (London BSI, 1987)
Ropes, Wire ropes, Steel-wire ropes, Strands, Cores (ropes), Diameter, Design, Breaking load, Tensile strength, Weight (mass), Rope pitch, Circular shape, Triangular shape, Mining equipment, Mine hoists, Grades (quality), Hoists, Lifts
Replaced By BS EN 12385-6:2004
Superseded, Withdrawn
Cross References BS 525, BS 2763, BS 5750:Part 2, BS 6570, ISO 2408, ISO 4344
Replaces BS 236:1968
Keywords: Steel-Wire Ropes -- Standards